Eradication of eucalyptus sprouts after chemical weeding over time in State of Bahia, Brazil - CAIQUE C. MEDAUAR; SAMUEL A. SILVA; LUIS CARLOS C. CARVALHO; RAFAEL A.S. TIBÚRCIO; JULIÃO S.S. LIMA; PHILIPPE S. OLIVEIRA (Anais da Academia Brasileira de Ciências, 2020)
Abstract This study evaluated the eradication of eucalyptus sprouts after chemical weeding using a diagrammatic scale over time. The research was conducted in fields planted with eucalyptus in forest reform areas, in Itabela, Bahia, Brazil, during the pre-planting herbicide application. The application was carried out in five fields, which were considered as sample units of the different treatments. The effectiveness of chemical weeding for controlling sprout growth was evaluated in fifty plants per treatment, randomly selected in three periods after application. The plants were evaluated visually using a diagrammatic scale to assign scores between 1 and 5 to the sprout control percentage. After the visual evaluations, the frequency distribution of the sprouting percentage for each score was calculated. Subsequently, the scores were submitted to a clustering analysis by the Ward method, to evaluate the relationship between different fields and periods for each treatment in homogeneous clusters. The results showed that treatments only controlled the sprouts in the short term, without providing effective eradication. The diagrammatic scoring scale allowed evaluating the vegetative vigor of the eucalyptus sprouts, generating interpretable information on the different evaluated treatments, making it a useful tool for managing silvicultural treatments and evaluating the application efficacy of phytosanitary products.